Pengaruh Gaya Kepemimpinan dan Budaya Organisasi Pada Kinerja Keuangan Dengan Penerapan Good Corporate Governance Sebagai Variabel Moderasi - Sudarsana, I Nyoman; Budiasih, I.G.A.N (E-Jurnal Akuntansi; Vol 29 No 1 (2019)DO - 10.24843/EJA.2019.v29.i01.p06, 2019)
This research was conducted to study leadership style and organizational culture on finance by implementing good corporate governance as a moderating variable. The theory used organizational behavior and the theory of conjunction. This research was conducted on 35 LPDs in Denpasar City. The sample in this study amounted to 35 respondents with the sample selection technique used was saturated sampling technique. The data collection method used questionnaire method. The data analysis technique used is the Moderating Regression Analysis (MRA) analysis technique. Research findings prove the variable leadership style and positive organizational culture on financial performance. Good corporate governance is able to moderate the leadership style of financial performance, but is not able to moderate the influence of culture on LPD financial performance in the city of Denpasar. Keywords : Ladership Style; Organizational Culture; Corporate Governance; Financial Performance; LPD.